Overcoming challenges in metagenomic AMR surveillance with nanopore sequencing: a case study on fluoroquinolone resistance - Bloemen, Bram; Gand, Mathieu; Ringenier, Moniek; Bogaerts, Bert; Vanneste, Kevin; Marchal, Kathleen; Roosens, Nancy H. C.; Dewulf, Jeroen; Boyen, Filip; De Keersmaecker, Sigrid C. J. (Frontiers in Microbiology, 2025)
IntroductionAntimicrobial resistance is an alarming public health problem, and comprehensive surveillance across environments is required to reduce its impact. Phenotypic testing and whole-genome sequencing of isolates are efficient, but culture-free approaches like metagenomic sequencing potentially allow for broader investigation of resistance gene occurrence, evolution and spread. However, technical challenges such as difficulties in associating antimicrobial resistance genes with their bacterial hosts and the collapse of strain-level variation during metagenome assembly, hinder its implementation.MethodsTo illustrate how these challenges can be overcome, we applied Oxford Nanopore Technologies long-read metagenomic sequencing and novel bioinformatic methods to a case study focused on fluoroquinolone resistance in chicken fecal samples.ResultsWe demonstrate plasmid-host linking based on detecting common DNA methylation signatures. Additionally, we use new bioinformatic approaches for strain haplotyping, enabling phylogenomic comparison and uncovering fluoroquinolone resistance determining point mutations in metagenomic datasets.DiscussionWe leverage long-read sequencing, including DNA methylation profiling and strain-level haplotyping, to identify antimicrobial resistance gene hosts, link plasmids to their bacterial carriers, and detect resistance-associated point mutations. Although some limitations remain, our work demonstrates how these improvements in metagenomic sequencing can enhance antimicrobial resistance surveillance.